Influence of Parents Attention, Emotional Intelligence and Learning Motivation to Learning Outcomes - Wahyuni Ambarwati (JETL (Journal of Education, Teaching and Learning), 2018)
In general this research is intended to build knowledge about the extent to which the attention of parents, emotional intelligence, motivation to learn effect student learning outcomes. Therefore, the authors make the title of research is "The Effect of Parents Attention, Emotional Intelligence and Learning Motivation of Learning Outcomes Learners Educate High School 4 Sampit at 2016/2017. The purpose of this study is to determine the effect of parents' attention, emotional intelligence and motivation to learn the outcomes of learners in SMA Negeri 4 Sampit at 2016/2017. The method used in this research is multiple linear regression analysis with 76 samples. The results showed that the attention of parents, emotional intelligence, and motivation to learn partially and simultaneously have a positive and significant impact on learning outcomes of learners.